Hydration status in adolescent alpine skiers during a training camp - Aerenhouts, D.; Chapelle, L.; Clarys, P.; Zinzen, E. (Journal of Human Kinetics, 2021)
Maintaining euhydration is important for optimal health, performance and recovery, but can be challenging for alpine skiers when training in a relatively cold but dry environment. This study aimed to evaluate hydration status, fluid loss and fluid intake in adolescent alpine skiers during a training camp. Twelve athletes aged 14.3 ± 0.9 years volunteered to participate in the study. Athletes resided at an altitude of 1600 m and trained between 1614 and 2164 m. During eight consecutive days, urine specific gravity wa s measured before each morning training session using a refractometer. Changes in body weight representing fluid loss and ad libitum fluid intake during each morning training session were assessed using a precision scale. Mean pre-training urine specific gravity remain ed stable throughout the training camp. Individual values ranged between 1.010 and 1.028 g/cm³ with 50 to 83% of athletes in a hypohydrated state (urine specific gravity = 1.020 g/cm³). Mean training induced fluid loss remained stable throughout the training camp (range -420 to -587 g) with in dividual losses up to 1197 g (-3.5%). Fluid intake wa s significantly lower than fluid loss during each training session. To conclude, urine specific gravity values before training indicated insufficient daily fluid intake in more than half of the athletes. Furthermore, fluid intake during training in adolescent alpine skiers was suboptimal even when drinks were provided ad libitum. Coaches and athlet es should be encouraged to carefully monitor hydration status and to ensure that alpine skiers drink sufficiently during and in between training sessions.